Effects of Energy Use on Socioeconomic Predictors in Africa: Synthesizing Evidence - Shobande, Olatunji Abdul (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2019)
The paper examined the effects of energy use on socioeconomic predictors in Africa. The Gary Becker hypothesis and the Michael Grossman demand for healthcare model were used to interact with energy related predictors on socioeconomic essentials. Our experimented model foretold the urgent need for government intervention programmes to resolve the energy misery in the African region.